Forage and seed yield of three Bromus species (Semiárida, 2020)
The objectives of this study were to evaluate the forage yield, protein content and seed yield of pampean bromegrass, rescue gran, and intermediate bromegrass experimental Iines. The cultivar "Don Lorenzo INTA" of intermediate bromegrass was used as reference. Two randomized complete block designs with 4 replicates were done, one for forage yield and protein contentand the other for seed yield and 1000 seed weight. ANOVA and FLSO tests (p
Keywords: Bromus; pampean bromegrass; intermediate bromegrass; rescue grass; forage yield; seed yield